Drew Pearson: as percepções de um jornalista norte-americano no contexto da Guerra Fria (1950-1957) - Portela, Leonice (2016)
This research focuses on the analysis of articles written by journalist Drew Pearson, published in the magazine O Cruzeiro, in a column named Carrossel do Mundo, during the decade of 1950. The American journalist Drew Pearson (1897-1969) was regarded as an international correspondent and an important investigative journalist. He signed the Carrossel do Mundo column, in the pages of O Cruzeiro, during the years 1947 to 1963. The magazine O Cruzeiro covered, in an impactful way, a significant and important historical period (1928-1975). Considered one of the milestones in the history of illustrated journalism of Brazil, the magazine was the periodic with the largest circulation in the country. O Cruzeiro is an important research source for researchers and historians from different areas and the content of its pages have allowed several studies. The reserach presented here is delimited by the years of 1950-1957, in the Cold War context, and aims to highlight the intersection of history and press and its discourse. The Cold War consisted in coping strategies that were restricted inside of a bipolar confrontation between the United States and the Soviet Union in their intense nuclear arms race, military movements and the winning of allies. The proposed analysis aims to understand the speech of Drew Pearson about Latin America countries on the matter of construction of the communist enemy, of the Soviet Union and the arms race during the Cold War power struggles. The research is oriented on the basis of methodological references of content and discourse analysis, using, as theoretical framework, the reflections on the discourse of the media and its influence on power relations. The analysis emphasizes primarily the speech of Drew Pearson, in order to realize the ideological and political conceptions that guided his articles, considering his perceptions on international relations of the United States as a central axis, as well as its relations with strategic and underdeveloped countries.